A Shift in Paradigms: Spatial Genomics Approaches to Reveal Single-Cell Principles of Genome Organization - Cardozo Gizzi, Andres M. (Frontiers in Genetics, 2021)
The genome tridimensional (3D) organization and its role towards the regulation of key cell processes such as transcription is currently a main question in biology. Interphase chromosomes are spatially segregated into “territories”, epigenetically-defined large domains of chromatin that interact to form “compartments” with common transcriptional status, and insulator-flanked domains called “topologically associating domains” (TADs). Moreover, chromatin organizes around nuclear structures such as lamina, speckles, or the nucleolus to acquire a higher-order genome organization. Due to recent technological advances, the different hierarchies are being solved. Particularly, advances in microscopy technologies are shedding light on the genome structure at multiple levels. Intriguingly, more and more reports point to high variability and stochasticity at the single-cell level. However, the functional consequences of such variability in genome conformation are still unsolved. Here, I will discuss the implication of the cell-to-cell heterogeneity at the different scales in the context of newly developed imaging approaches, particularly multiplexed FISH methods that enabled “chromatin tracing”. Extensions of these methods are now combining spatial information of dozens to thousands of genomic loci with the localization of nuclear features such as the nucleolus, nuclear speckles, or even histone modifications, creating the fast-moving field of “spatial genomics”. As our view of genome organization shifts the focus from ensemble to single-cell, new insights to fundamental questions begin to emerge.